Effectiveness of the Immigration Medical Surveillance Program for Tuberculosis in Ontario - Uppaluri, Aparna (Can J Public Health, 2002)
Background: Citizenship and Immigration Canada (CIC) screens immigrants for TB and permits those with inactive pulmonary TB to enter Canada conditionally, subject to medical surveillance; we studied this program in Ontario. Method: This was an administrative database study with linkage of national and provincial data. Results: In 1994–95, 1,341 cases of foreign-born active TB were diagnosed and a CIC record was found for 1,095. 149 (14%) were classified for surveillance and 142 were included in the analysis. A significant proportion (39/142: 27%) were diagnosed either before or as a result of immigration screening in Canada. These persons had arrived as visitors or refugees and were excluded from further analysis. Only 21 of the remaining 103 persons (20%) with immigration screening before the diagnosis of TB adhered to surveillance. Only 1 of 16 (6%) eligible persons was given therapy to prevent future episodes of active TB. Most presented with symptoms (82/103: 82%) suggesting potential for TB transmission in Ontario. Interpretation: The current TB surveillance system for high-risk immigrants to Ontario is not effective in identifying and treating latent infection, and thus not effective in preventing future cases.